Efektivitas Ekstrak Daun Pepaya (Carica papaya L.) sebagai Wound Healing Menggunakan Ikan Zebra Danio rerio Hamilton, 1822 Yang Diinduksi Hiperglikemia sebagai Model - Aini, Falihah Nur; Elfita, Lina; Fitriana, Narti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
Papaya leaves are known to have antidiabetic and wound-healing activities because they contain flavonoids, alkaloids, tannins, and saponins. Tests of the activity of papaya leaf extract in mouse models have been widely conducted. In this study, the wound healing activity of papaya leaves was carried out using zebrafish as a model, because of their ability to regenerate and 70% similarity to human glucose metabolism. This study aimed to analyze the potential of zebrafish as a model for healing diabetic wounds using 96% ethanol extract from papaya leaves. Zebrafish were divided into six groups, namely normal control, negative control, positive, and papaya leaf extract 125, 187.5, and 250 ppm. The parameters observed were a decrease in blood sugar levels, regeneration of the zebrafish caudal fin, and survival rate of the fish. The results showed that there was an effect of administering papaya leaf extract at doses of 125, 187.5, and 250 ppm respectively to reduce blood sugar levels by an average of 42.67; 44.33; and 72 mg/dL, an increase in fin length of 1; 1.3; 1 mm, and survival rate with a percentage of 91%, 91%, 64%. It was concluded that zebrafish could be used as a test model for diabetic wound healing. Apart from that, the use of 96% ethanol extract from papaya leaves affects the healing of diabetic wounds. Of the 3 doses given with 96% ethanol extract of papaya leaves, the best dose for healing diabetic wounds was 187.5 ppm.